2014
DOI: 10.21149/spm.v56i1.7324
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance and molecular epidemiology of Mycobacterium tuberculosis in Mexico: A systematic review

Abstract: Objective. To compare drug resistance (DR) rates and genetic diversity of Mycobacterium tuberculosis strains from different states of Mexico. Materials and methods. A systematic review of English and Spanish-language articles using MEDLINE and Google Scholar. Search terms included Mycobacterium tuberculosis, Mexico, resistance, mutation and epidemiology. Results. Fifteen studies for phenotypic DR rates (n=2 694), twelve studies for genotypic DR (n=748) and eleven studies for genetic diversity (n=2 044) met our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
5
20
0
Order By: Relevance
“…The most predominant clades found in our study were the ill-defined T clade (SIT53), the Haarlem clade (SIT50), the Latin American-Mediterranean clade (SIT42) and the IS 6110 -low-banding X clade (SIT137). These results are similar to those reported in several studies from across the country [ 8 – 17 ]. And considering that SIT42 evolved originally from SIT53, this group is very dominant in this region [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The most predominant clades found in our study were the ill-defined T clade (SIT53), the Haarlem clade (SIT50), the Latin American-Mediterranean clade (SIT42) and the IS 6110 -low-banding X clade (SIT137). These results are similar to those reported in several studies from across the country [ 8 – 17 ]. And considering that SIT42 evolved originally from SIT53, this group is very dominant in this region [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although a high number of previously reported spoligotypes were identified in Mexico [ 12 , 13 , 17 ], 19.1% of our isolates showed SIT (335, 371, 406, 469, 1231, 1686, 2007, 2212 and 3434) which were previously unreported in the country.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…We identified 32 SITs, of which 17 (53%) (1, 2, 19, 20, 42, 46, 49, 50, 51, 53, 92, 119, 291, 334, 948, 787 and 2212) had been previously described in DR-TB and MDR-TB isolates circulating in Mexico [ 18 , 19 ], and other Latin American countries [ 40 , 41 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the control sample set of 58 PTB DNAs, showed that 26 (44.8%) strains, which included 84.6% Beijing, 11.5% T1 and 3.8% T2 genotypes, were resistant to at least 1 drug. There were 10 strains (17.2%), 9 Beijing and 1 T1 that were of MDR type, resistant to at least INH (Ser 315 Thr in KatG) and RIF (Ser 531 Leu in RpoB), the 2 most powerful anti-TB drugs (33). The proportion of MDR-TB in the Beijing vs. non-Beijing genotype PTB strains was statistically different (p < 0.02).…”
Section: Molecular Screens For Drug Resistancementioning
confidence: 97%